2018
DOI: 10.3892/etm.2018.6346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NMDA on proliferation and apoptosis in hippocampal neural stem cells treated with MK‑801

Abstract: The purpose of the present study was to investigate effects of N-methyl-D-aspartate (NMDA) on proliferation and apoptosis of hippocampal neural stem cells (NSCs) treated with dizocilpine (MK-801). Cultures of hippocampal NSCs were randomly divided into four groups consisting of an untreated control, cells treated with MK-801, NMDA and a combination of MK801 and NMDA (M+N). Proliferative and apoptotic responses for each of the experimental groups were determined by MTS and flow cytometry. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
2
2
0
1
Order By: Relevance
“…More specifically, regarding the dorsal telencephalon, the densities of mitotically active cells were decreased in the proliferation zones of Dm and Dld, two putative homolog structures of basolateral amygdala (BLA) and hippocampus of mammals ( O'Connell and Hofmann, 2011 ), regulating both social behavior ( Bickart et al, 2014 ; FeldmanHall et al, 2021 ) as well as fear and anxiety-like responses ( Lal et al, 2018 ; Ghasemi et al, 2022 ). Our results further support previous evidence on decreased hippocampal NSPCs proliferation by NMDAR hypofunction ( Maeda et al, 2007 ; Song et al, 2016 ; Ding et al, 2018 ). Moreover, in rodent animal models, chronic stress or deficits in social communication are characterized by the dysregulation of different stages in postnatal hippocampal neurogenesis including neural progenitor proliferation and differentiation ( Malberg and Duman, 2003 ; Heine et al, 2004 ; Hong et al, 2019 ; Gioia et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, regarding the dorsal telencephalon, the densities of mitotically active cells were decreased in the proliferation zones of Dm and Dld, two putative homolog structures of basolateral amygdala (BLA) and hippocampus of mammals ( O'Connell and Hofmann, 2011 ), regulating both social behavior ( Bickart et al, 2014 ; FeldmanHall et al, 2021 ) as well as fear and anxiety-like responses ( Lal et al, 2018 ; Ghasemi et al, 2022 ). Our results further support previous evidence on decreased hippocampal NSPCs proliferation by NMDAR hypofunction ( Maeda et al, 2007 ; Song et al, 2016 ; Ding et al, 2018 ). Moreover, in rodent animal models, chronic stress or deficits in social communication are characterized by the dysregulation of different stages in postnatal hippocampal neurogenesis including neural progenitor proliferation and differentiation ( Malberg and Duman, 2003 ; Heine et al, 2004 ; Hong et al, 2019 ; Gioia et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, MK801 for as little as 24 h enhanced astrocyte viability, as measured by MMT assay. Ding et al (2018) found that neural stem cell proliferation and viability were significantly reduced by MK-801 treatment for 24 h, but the concentration of MK-801 was high enough (200 µM) to induce significant apoptosis (Ding et al, 2018). Consistent with the present results, MK-801 enhanced expression of the astrocyte-specific intermediate filament protein GFAP, a marker of cell activation in response to local brain injury (Yu et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Inhibition of NMDAR by MK801 leads to apoptosis of neurons [ 65 , 66 ]. MK-801 also inhibits proliferation and increases apoptosis in hippocampal neural stem cells [ 67 ]. We found that the upregulation of DDIT4 expression in the hippocampus by sevoflurane can be inhibited through the supplementation of NMDA in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%